Charge‐Separated and Lewis Paired Metal–Organic Framework for Anion Exchange and CO2 Chemical Fixation. Issue 61 (16th October 2020) - Thapa, Sheela; Meng, Lingyao; Hettiarachchi, Eshani; Bader, Yousef K.; Dickie, Diane A.; Rubasinghege, Gayan; Ivanov, Sergei A.; Vreeland, Erika C.; Qin, Yang
Abstract: Charge‐separated metal–organic frameworks (MOFs) are a unique class of MOFs that can possess added properties originating from the exposed ionic species. A new charge‐separated MOF, namely, UNM‐6 synthesized from a tetrahedral borate ligand and Co 2+ cation is reported herein. UNM‐6 crystalizes into the highly symmetric P 43 n space group with fourfold interpenetration, despite the stoichiometric imbalance between the B and Co atoms, which also leads to loosely bound NO3 − anions within the crystal structure. These NO3 − ions can be quantitatively exchanged with various other anions, leading to Lewis acid (Co 2+ ) and Lewis base (anions) pairs within the pores and potentially cooperative catalytic activities. For example, UNM‐6‐Br, the MOF after anion exchange with Br − anions, displays high catalytic activity and stability in reactions of CO2 chemical fixation into cyclic carbonates. Abstract : Cyclic carbonates : Charge‐separated metal–organic framework that contains exposed Lewis acidic metal ions and loosely bound Lewis basic anions offers unique properties for anion exchange and CO2 chemical fixation applications.